Ministry of Public Utilities - (:unkn) unknown (My University, 2011)
CORPORATE VISION An organization dedicated to excellence and equity in the delivery of public utilities and sustainability of our country, and an improved quality of its citizenry. MISSION To facilitate the delivery of affordable and quality public utilities, through a committed, resourceful team of professionals in close collaboration with all partners.
Keywords: Public Utilities